2023
DOI: 10.1111/mmi.15150
|View full text |Cite
|
Sign up to set email alerts
|

PASTA‐kinase‐mediated signaling drives accumulation of the peptidoglycan synthesis protein MurAA to promote cephalosporin resistance in Enterococcus faecalis

Carly A. Mascari,
Jaime L. Little,
Christopher J. Kristich

Abstract: The bacterial PASTA kinase, IreK, is required for intrinsic cephalosporin resistance in the Gram‐positive opportunistic pathogen, Enterococcus faecalis. IreK activity is enhanced in response to cell wall stress, such as cephalosporin exposure. The downstream consequences of IreK activation are not well understood in E. faecalis, but recent work in other low‐GC Gram‐positive bacteria demonstrated PASTA kinase‐dependent regulation of MurAA, an enzyme that performs the first committed step in the peptidoglycan sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 92 publications
3
26
0
Order By: Relevance
“…The involvement of the IreK Ser/Thr-protein kinase, IreP Ser/ Thr-protein phosphatase, IreB regulatory protein, and ClpP protease from these new and past results (Kelliher et al, 2021;Sun et al, 2023;Wamp et al, 2020Wamp et al, , 2022 Notably, relative cellular MurAA amount also increased in cells treated with a sublethal concentration of ceftriaxone (Mascari et al, 2023), which activated protein phosphorylation by the IreK Ser/Thr-protein kinase (Labbe & Kristich, 2017;Minton et al, 2022).…”
Section: Muraamentioning
confidence: 81%
See 4 more Smart Citations
“…The involvement of the IreK Ser/Thr-protein kinase, IreP Ser/ Thr-protein phosphatase, IreB regulatory protein, and ClpP protease from these new and past results (Kelliher et al, 2021;Sun et al, 2023;Wamp et al, 2020Wamp et al, , 2022 Notably, relative cellular MurAA amount also increased in cells treated with a sublethal concentration of ceftriaxone (Mascari et al, 2023), which activated protein phosphorylation by the IreK Ser/Thr-protein kinase (Labbe & Kristich, 2017;Minton et al, 2022).…”
Section: Muraamentioning
confidence: 81%
“…Together, these results suggested that unphosphorylated IreB was a negative regulator of a downstream factor that contributed to cephalosporin resistance (Hall et al, 2013;Kristich et al, 2007). These findings also provided a framework for interpretation of IreB/ReoM function in the other F I G U R E 1 Regulatory pathway that leads to destabilization of MurAA by binding to unphosphorylated IreB in Enterococcus faecalis proposed in (Mascari et al, 2023). Cell wall stresses signal the IreK Ser/Thr-protein kinase to transfer a phosphoryl group from ATP to the IreB regulatory protein.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations